Comparison of subsidy schemes for carbon capture utilization and storage (CCUS) investment based on real option approach: Evidence from China. (1st December 2019) - Yang, Lin; Xu, Mao; Yang, Yuantao; Fan, Jingli; Zhang, Xian
Highlights: Real option approach is adopted to analyze subsidy for the CCUS project. Even full investment subsidy cannot stimulate investment immediately. Both electricity tariff subsidy and CO2 utilization subsidy are feasible. Electricity tariff subsidy is higher than the current subsidy for renewable energy. CO2 utilization subsidy is more favorable for developing full-chain CCUS project. Abstract: This study adopts the real option approach to compare the impacts of different subsidy schemes, including initial investment subsidy, electricity tariff subsidy, and CO2 utilization subsidy, on the investment benefit of carbon capture utilization and storage (CCUS) project in China under high, medium, and low coal price levels, respectively. The results show that: (1) Under the current oil price level (70 USD/bbl), CO2 utilization subsidy referring to the 45Q Tax Credit released by the US government is high enough to trigger the investment behavior immediately. However, the full initial investment subsidy needs to be replenished with other ways and the electricity tariff subsidy needs to increase by 2.6 times compared with the current subsidy for renewable energy (0.019 CNY/kWh). (2) The critical oil prices under full investment subsidy and electricity tariff subsidy need to increase by at least 2.7% and 14.1%, respectively. (3) Both electricity tariff subsidy and CO2 utilization subsidy are feasible, while the former need to exceed the current subsidy for renewable energy and the latter is more favorable in promoting the development of full-chain CCUS project and the increase of oil production. (4) The optimal investment timing can be brought forward to 2023 if the technological learning rate reaches 30% under the low coal price level; the investors should abandon the project until the technological learning rates reach 5% and 10% under the medium and high coal price levels, respectively. Overall, our results enable to provide useful information for the policy-makers to formulate subsidy policies.